2022
DOI: 10.3390/children9020123
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Attitudes on Early Identification Practices of Autism: A Preliminary Survey of Pediatric Professionals in Ecuador

Abstract: Early identification of children with autism is necessary to support their social and communicative skills and cognitive, verbal, and adaptive development. Researchers have identified several barriers to early diagnosis. Data collected in low- and middle-income contexts—where the vast majority of children in the world live—is scarce. In Ecuador, as in many other countries, estimates are lower compared to the global prevalence. Health authorities estimate a prevalence of 0.28% (0.18%–0.41%) in children aged fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Universities offer postgraduate education in pediatrics; however, the specific pedo-psychiatric and neuro-pediatric fields rely on interns trained in other countries who return to work in Ecuador. In the pediatric sector, professionals may face many challenges in ASD case-identification and case-management, such as access to training and available resources to refer families ( Buffle et al, 2022 ). The public health system has two pediatric hospitals in two main cities, and several community centers around the county and units providing specific ASD services of identification and treatment are currently being developed.…”
Section: Introductionmentioning
confidence: 99%
“…Universities offer postgraduate education in pediatrics; however, the specific pedo-psychiatric and neuro-pediatric fields rely on interns trained in other countries who return to work in Ecuador. In the pediatric sector, professionals may face many challenges in ASD case-identification and case-management, such as access to training and available resources to refer families ( Buffle et al, 2022 ). The public health system has two pediatric hospitals in two main cities, and several community centers around the county and units providing specific ASD services of identification and treatment are currently being developed.…”
Section: Introductionmentioning
confidence: 99%
“…This procedure can play an important role in primary care routines. Combined with a short, validated and culturally adapted questionnaire, it can contribute to eliminating barriers to screening and identification that have previously been reported by Ecuadorian paediatricians ( Buffle & Gentaz, 2019 ; Buffle et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The participants also perceived ASD-specific questionnaires as ‘not useful if a child is showing a normal development’, ‘lack of reliability on parental responses’ and ‘non-comfortable’ or ‘difficult to find’ as the main drawbacks. A second study ( Buffle et al, 2022 ), conducted on 183 paediatric professionals, indicated a low number of cases of autism identified during participant’s professional life, with 62% of participants reporting not having identified ASD cases during their professional life. This study also identified several barriers consistent with those identified in other countries, including limited knowledge of screening formal application, lack of time, lack of resources to refer and information to provide families, and fear of unnecessarily alarming families ( Buffle et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, diagnosing autism is particularly burdensome in early childhood due to the complexity of ASD development and etiopathogenesis, which compels physicians to endeavor novel diagnostic strategies ( 64 71 ). The topic of oral, dental, and periodontal health in the early pediatric life of ASD subjects is still missing from the correct management of these individuals by pediatricians and pediatric dentistry ( 72 , 73 ).…”
Section: Oral Health Prevention In the Autistic Subject As Early As P...mentioning
confidence: 99%